Pengaruh Tipe Kepribadian Dan Penggunaan Smartphone Terhadap Hasil Belajar Mata Pelajaran Ekonomi - Lusi Eka Lestari; Z Mawardi Effendi (Jurnal Ecogen, 2021)
This study examined to describe the effect of personality type and smartphone use on economic learning outcomes in class XI IPS at SMA Negeri 3 Kota Solok for the 2019/2020. Type of this study is associative quantitative. Population in this study is students of class XI IPS at SMA Negeri 3 Kota Solok 2019/2020, and sample in this study obtained using the slovin formula with proportional random sampling technique. Data analyse technique used is descriptive and quantitative analyse with multiple linear regression. The result of this study showed that 1) Personality type have a positive effect and significant on the economic learning outcomes with sig 0,006 < 0,05. 2) Smartphone use have a negative effect and not significan on the economic learning outcomes with sig 0,640 < 0,05. 3) Personality type and smartphone use have together effect on the economic learning outcomes with sig 0,009 < 0,05.Keywords : learning outcomes, personality type, smartphone used